MIGRASI PASCA-PERANG DUNIA II DAN MULTIKULTURALISME DI AUSTRALIA - Suharyadi , Irsyaad; Nahida , Najwa Aziza (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This study examines the role of post-World War II migration and cultural globalization in shaping Australia’s national and regional identity. The end of World War II marked a critical turning point in Australia’s demographic and policy orientation, particularly through the expansion of immigration programs and the gradual dismantling of the White Australia Policy. Drawing upon a qualitative descriptive approach with a historical-analytical method, this research analyzes secondary data from academic literature, policy documents, and international reports to explore the interplay between migration flows, global cultural exchanges, and identity construction. The findings reveal that large-scale migration not only transformed Australia’s demographic composition but also facilitated the emergence of multiculturalism as a defining feature of its national identity. Through processes of cultural interaction, adaptation, and hybridization, migrants contributed to the formation of new social practices and urban cultural landscapes. However, the study also highlights that the construction of a multicultural identity is neither linear nor uncontested. Persistent challenges such as racism, social exclusion, and unequal integration continue to shape the limits of multiculturalism in Australia. From a constructivist perspective in International Relations, this study argues that identity is socially constructed through historical processes, policy frameworks, and transnational interactions. Australia’s evolving identity reflects not only domestic transformations but also its repositioning within the Indo-Pacific region and the broader global order. By linking migration, globalization, and identity, this study contributes to a deeper understanding of how states negotiate internal diversity while projecting their identity externally in international relations.